Pendidikan Islam di Indonesia dari Masa ke Masa - Sarno Hanipudin (Matan : Journal of Islam and Muslim Society, 2019)
Islamic education in Indonesia seems to be filled with problems, explicitly this happens in the context of history: in the colonial period, Islamic education based on pesantren, where at the same time also the colonial government has the same mission of establishing missionary schools. at that time pesantren and madrasah served as the target of the Dutch colonial government's political targets, as the center of the Muslim resistance. However, soon after independence, Islamic education got a lot of change by adopting various educational systems, by including various subjects that come from non-Muslims. In the next stage the reconstruction of education reaches the desired stage of the decree of three ministers, which makes the position of the madrasah equivalent to formal education. This study attempts to re-narrate the journey of Islamic education in Indonesia from pre-independence to the present.